Association of clinical and laboratory data of rural area residents to chronic exposure to glyphosate (Research, Society and Development, 2021)
Commonly used by farmers, glyphosate has become the subject of many studies in recent years. However, these studies investigate and correlate glyphosate exposure to the most diverse physiological, motor, sensory, respiratory and hepatic functions, and possibly be related to causes of carcinogenicity and genotoxicity. Thus, the objective of the present study was to evaluate whether the population living in rural area of Paraguaçu, Brazil, presents evidence of chronic intoxication by glyphosate-based formulations through the evaluation of clinical signs and symptoms and laboratory data. A total of 162 samples were collected and analyzed using 53 samples from individuals who reported no contact with glyphosate for the control sample. Biochemical analyzes were performed on automated equipment, while cholinesterase was performed by Ellman's kinetic method. Data were submitted to statistical analysis, where changes in the nervous, respiratory, auditory, cutaneous and urinary systems were observed. Through the analysis of the data, associated with the literature information on the symptoms and damage generated by glyphosate, it can be concluded that the population living in the rural area, practicing family farming, has strong indications of having chronic poisoning by formulations based on glyphosate.